The Future Positive micro-intervention protocol: A program aiming to increase a healthy life-style among employees with a low socio-economic position - Schelleman-Offermans, Karen; Ruiter, Robert A. C.; Massar, Karlijn (Frontiers in Public Health, 2022)
This paper describes the development of a Dutch micro-intervention, Future Positive, that aims to increase health behaviors among employees with a low socio-economic position (SEP), with the ultimate aim to decrease socio-economic health inequalities. Intervention Mapping (IM) was used to adapt previously developed psychological capital interventions into a micro-intervention suitable to be delivered in the work context for employees with a low socio-economic position. The first 4 steps of IM including the results of pre-testing the developed intervention program are described. Step 1 consists of the needs assessment, and investigated (a) the individual determinants of health behavior and health inequalities, and (b) the needs of employees with a low SEP and their employers regarding the implementation of the intervention at the worksite. Matrices-of-change were produced in Step 2, and relevant methods and applications were selected in step 3. Step 4 involved the intervention development, resulting in a brief micro-intervention that will be delivered in small groups, guided by trained facilitators using motivational interviewing techniques. Program materials include informative video-clips and active and cooperative learning exercises. The intervention was pre-tested among three groups of employees. The IM process, as well as the pre-testing, revealed that emphasizing autonomy and using easy to understand and mostly visual materials offered in chunks is essential for a well-tailored intervention that is suitable for people with low SEP. Also, participation should be facilitated by employers: It should be free of costs, offered during working hours, and take place at the job site. Results showed that the Future Positive micro-intervention is substantiated by theory, applicable in a work setting (high reach), and tailored to the needs of employees with a low SEP. We therefore fill the gap in this existing range of interventions aimed to improve life-style behaviours and contribute to theory-based interventions aimed to decrease the SEP-Health gradient.